PERAN KOMUNITAS SAVE STREET CHILD DALAM MENINGKATKAN PENDIDIKAN MORAL ANAK JALANAN DI MALANG - Chusainiyah, Feni Dwi Erni; Liestyasari, Siany Indria; Zuhri, Saifuddin (Jurnal Al-Fatih, 2024)
This study aims to examine the role of Save Street Child community in improving moral education of street children in Malang City. This research is aqualitative descriptive research. Data sources of this study include primary data sources through observations made during Save Street Child community activities in Malang City and interviews addressed to Chairmen and administrators, Volunteers and street children who participated in Save Street Child community activities and secondary data sources through photo documentation obtained during Save Street Child Malang community activities. The informant retrieval technique is carried out by nonprobability purposive sampling. Data collection is carried out by observation, interview and documentation techniques. The data validity test technique uses the source triangulation technique. Data analysis techniques using Miles & Huberman techniques. The results of this study are as follows. First, the moral condition of street children in the save street child community in Malang still requires knowledge and cultivation of the importance of moral education in the neighborhood. Second, the role through activities and programs provided by the save street child Malang community provides good changes for street children in the save street child Malang community, such as: individual and group assistance and guidance and the implementation of programs.